2017
DOI: 10.1186/s13567-017-0415-8
|View full text |Cite
|
Sign up to set email alerts
|

Counts of bovine monocyte subsets prior to calving are predictive for postpartum occurrence of mastitis and metritis

Abstract: The heightened susceptibility to infectious diseases in postpartum dairy cows is often attributed to immune dysfunction associated with the transition period. However, the cell populations involved in this immune dysfunction and the dynamics between those populations are not well defined. Monocytes play a crucial role in governing initial immune response in bacterial infections. Bovine monocytes are subdivided in classical (CD14+/CD16−), intermediate (CD14+/CD16+) and non-classical monocytes (CD14−/CD16+) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…Studies in different species revealed that monocytes are a heterogeneous population of innate immune cells consisting of phenotypically and functionally different subsets [4][5][6][7][8][9][10][11]. The clinical relevance of distinct monocyte subsets has been recently demonstrated for different species by linking the distribution of blood monocyte subsets to the susceptibility to different infectious [20] and non-infectious diseases [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in different species revealed that monocytes are a heterogeneous population of innate immune cells consisting of phenotypically and functionally different subsets [4][5][6][7][8][9][10][11]. The clinical relevance of distinct monocyte subsets has been recently demonstrated for different species by linking the distribution of blood monocyte subsets to the susceptibility to different infectious [20] and non-infectious diseases [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between prepartum cell composition of bovine monocyte subsets and the occurrence of mastitis or endometritis postpartum has been recently analyzed ( 89 ). The study has shown that the composition of monocyte subsets before calving is in relation to the susceptibility of cows to infectious diseases within 2 weeks postpartum.…”
Section: Clinical Relevance Of Bovine Monocyte Subsetsmentioning
confidence: 99%
“…Studies in different species revealed that monocytes are a heterogeneous population of innate immune cells consisting of phenotypically and functionally different subsets [4][5][6][7][8][9][10][11]. The clinical relevance of distinct monocyte subsets has been recently demonstrated for different species by linking the distribution of blood monocyte subsets to the susceptibility to different infectious [17] and noninfectious diseases [18,19].…”
Section: Discussionmentioning
confidence: 99%